МОНИТОРИНГ ЭПИЗООТИЧЕСКОЙ СИТУАЦИИ ПО БРУЦЕЛЛЕЗУ ЖИВОТНЫХ В КАЗАХСТАНЕ 2025 ГОДУ - Е. Оспанов; А. Адамбаева; А. Арысбекова; Е. Шакибаев; М. Маталипова; Г. Кыдырова; Н. Көшкінбай; Б. Орынбаева; Г. Бойко; М. Кадыркулова; Е. Щелкунова; Р. Куанов; et al. (Animal Health and Biosafety, 2026)
In this article, brucellosis is considered as one of the most urgent veterinary problems, which has a significant impact on the epizootic situation in Kazakhstan. The urgency of the problem is reinforced by the instability of the epizootic situation, which necessitates constant monitoring and the introduction of effective preventive measures to reduce the risk of infection and improve the health of disadvantaged farms. In 2025, visits were conducted to various regions of the country to select biological material. A total of 14030 samples were taken, of which 6320 were from cattle and 6295 from small cattle. Serological studies have shown an average infection rate in farms where infected cattle were detected – 7,43%, and small cattle -6,29%. Sick animals were detected in 27 epizootological units, and in 5 of them positive reactions were detected in both large and small cattle. The total incidence of epizootological units was 38.02%. The average incidence rates of brucellosis in the republic in 2025 were: for cattle – 28,16%, for small – 16,90%. Based on the data obtained, a zoning map of the territory of the Republic of Kazakhstan was compiled according to the degree of brucellosis incidence in animals using GIS technologies. Areas where the incidence rate of cattle is lower than the national average (2,53%) are classified as low–risk areas, and higher - as high-risk areas. It is the same for small cattle: areas with a level above 1,18% are defined as areas of high morbidity. The inter-regional differences and instability of indicators by year reflect the intensity of the epizootic situation and the presence of high-risk zones. The data obtained emphasize the need to improve the system of veterinary supervision and prevention in disadvantaged regions, as well as to apply an integrated and differentiated approach to the control of brucellosis.